(untitled) (Bangladesh Journal of Botany, 2021)
Problems of poor soil structure and nutrient deficiency in the reclamation of abandoned homesteads, and improvement of the soil condition after land reclamation to arable land and rapidly resume agricultural production were investigated. Organic fertilizers, curing agent and fly ash as amendment materials were selected. A plot test with seven different return materials in order to obtain the effects of different amendment materials on nutrient improvement in the reclamation of abandoned homestead soils in loess areas was conducted. After 3 years of maize crop cultivation, soil samples were collected and analyzed for total soil nitrogen content under different treatments. The results showed that the maize yield in each plot showed different additives contributed to the increase in maize yield to different degrees, while the addition of organic fertilizer had a more significant effect on the increase in yield. In the treatment of the experimental plots with the addition of curing agent + organic fertilizer, there was a significant effect on the enhancement of the content of total nitrogen in the soil tillage layer after three years of maize cultivation. The total N content of the surface soil (0 15 cm) increased from 0.32 to 0.64 g/kg, and that of the soil from 15 30 cm increased from 0.31 to 0.66 g/kg. The total N content of the soil from 0 60cm showed an increasing trend year by year, but the increase was gradually reduced. The total nitrogen content of soil in the depth of 60 105 cm showed a decreasing trend year by year. In the remediation of hollow villages in loess plateau, the compound application of organic fertilizer and ripening agent can significantly improve the soil nutrient content, condition of farmland and increase in maize yield, which is the most suitable material for field return in the remediation of hollow villages in loess plateau, and is of great significance to improve the quality of field return in the remediation of hollow villages. Bangladesh J. Bot. 50(3): 729-736, 2021 (September) Special